Розширення температурного діапазону експлуатації фільтруючих матеріалів на основі політетрафторетилену шляхом армування полімерної матриці - Ісаєв, М.; Калюжний, О.; Платков, В. (Науковий журнал «Інженерія природокористування», 2021)
In order to increase the stability of the pore space of porous polytetrafluoroethylene (PTFE) at ele-vated temperatures, composites based on commercial PTFE have been prepared. Highly refined MG-1 graphite and activated carbon powder were used as reinforcing materials. Deformation curves and hardness values of HRB PTFE and composites based on it were obtained. A technological process of the production of porous composites based on PTFE with a polymer matrix reinforced with graphite MG-1 has been developed. The sodium chloride was used as a porogen, which was removed from the semi-finished products by leaching for the production of bulk porous composites with open porosity and controlled pore structure.The porous materials based on PTFE with a porosity of  and porous PTFE-based compo-sites reinforced with graphite with the same porosity, were obtained.Optical microscopic studies of porous PTFE and porous composite based on PTFE reinforced with graphite showed the identity of their pore structures. A method is proposed for assessing the homogeneity of pore structures by means of multiple measurements of microhardness in various areas of porous polymers. It was found that the developed technological process for production of porous PTFE and a porous composite based on PTFE reinforced with graphite ensures the formation of homogeneous pore structures.The values of the microhardness of porous PTFE have been obtained. The graphite reinforcement of the polymer matrix is shown to decreas the elasticity and increas the strength of their interpore parti-tions. This made it possible to obtain filter materials capable of maintaining the specified parameters of the pore structure and operating reliably at elevated temperatures up to 250.